Tanzania Education Sector Institutional and Governance Assessment - World Bank (World Bank, Washington, DC, 2021)
The Tanzania Education Sector Institutional and Governance Assessment (hereafter referred to as the report) identifies the drivers of efficient and effective basic education service delivery in Tanzania by exploring the sector’s institutional and governance context. The assessment has four main components: i) the policy and institutional setting; ii) the public financial management (PFM) context; iii) decentralization and its impact on basic education; and iv) school autonomy and accountability in the delivery of education services. Viewing these through a ‘service delivery lens’, the report presents the key findings and recommendations for medium-term as well as immediate future programming aimed at improved learning outcomes in Tanzania. The report takes an overall systems approach where each component is viewed as part of the whole, to create a picture where interconnected systemic constraints underpin an uncertain accountability chain. This is presented as a synthesis of learnings across all four components. The picture that emerges informs the recommendations of the Report, enabling the identification of synergistic critical pathways and entry-points for effective, efficient, and accountable education service delivery and, in the longer term, improved learning outcomes.